Developing Interactive Speaking Flashcards Integrated with Revised Bloom’s Taxonomy for Junior High School Students - Ferry Desryananda; Bambang Irfani; Zakiyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Speaking remains a challenging skill for junior high school students in English as a Foreign Language (EFL) context, as classroom activities often emphasize lower-order cognitive tasks and provide limited support for structured oral expression. This study aimed to develop interactive speaking flashcards integrated with Revised Bloom’s Taxonomy to facilitate HOTS-oriented speaking tasks, specifically analyzing (C4), evaluating (C5), and creating (C6). Using a Research and Development (R&D) approach, the study produced three types of flashcards, story/scenario, multiple-choice, and game-based, designed to guide students through cognitively structured speaking activities. The product was validated by experts and implemented in a small-scale classroom tryout. Expert validation results showed that the flashcards achieved valid to very valid categories, with mean scores of 3.47 (language), 4.53 (media), and 4.20 (content), supported by acceptable content validity based on Aiken’s V. Classroom implementation indicated that the flashcards were practically usable within a 25-minute lesson, as all implementation indicators were fulfilled (100% observation score). Students’ responses, measured through a Self-Determination Theory–based questionnaire, showed high agreement across autonomy (M = 3.93), competence (M = 3.92), and relatedness (M = 3.90). Overall, the findings indicate that the developed flashcards are feasible and practical instructional media for supporting structured, HOTS-oriented speaking tasks in junior high school EFL classrooms.